Does Training Enhance Professional Practice in Infant Mental Health?. Issue 3 (26th May 2020) - Hughes, Teresa; McGlade, Anne; Killick, Campbell
Abstract : The lack of robust evaluation of training outcomes has been noted within the delivery of Health & Social Care across the UK. The impact on adult mental health of poor emotional care during infancy and early childhood has also been highlighted by the relatively recent advancements in neuroscience. This study used pre- and post-testing to assess practice across three key domains. The gains observed in staff knowledge and confidence post-training are directly attributable to the training: p < .001 (Knowledge Scores) and p = .001 (Self-Efficacy Scores). Key findings also indicate that Infant Mental Health (IMH) training has potential to encourage staff in Adult Services to take more ownership of a family focused agenda and that current service provision struggles to meet the needs of high-risk infants. With a clear focus on robust methodology, this study measures IMH training outcomes on a multi-professional basis across Adult Mental Health and Children's Services within one Health & Social Care Trust (NI). The findings also add to our understanding of the interface between social work and other services who seek to support families with complex needs.